THE USE OF ELECTRONIC DICTIONARIES AND PRACTICAL SOFTWARE IN THE STUDY OF FOREIGN LANGUAGES (Archive of Conferences, 2021)
The introduction of Information Communication Technology into the educational process is becoming increasingly important, especially in the teaching and learning of foreign languages. New information technology offers great opportunities in teaching foreign languages, plays an important role in obtaining quality knowledge in science and increasing the effectiveness of Education